TACNA AND ARICA DURING THE PACIFIC WAR IN THE AMERICAN PRESS(1880) (Tzintzun, Revista de Estudios Históricos, 2024)
The article, which addresses the War of the Pacific during its development inTacna and Arica, aims to explain the construction of imaginaries towards Peru,Bolivia and Chile in the US press. The content analysis carried out on thenewspapers allows us to conclude that the imaginary about Peru was damagedby the “morality” of its political-military leaders; that of Bolivia represented apoor and disorganized country; and that of Chile emerged as an ambivalent state:organized, but barbarous.
Keywords: War of the Pacific; Tacna; Arica; Chile; Perú; Bolivia